EFFECTIVENESS OF COCONUT WATER AND RED GINGER ON DECREASING EMESIS GRAVIDARUM AT TPMB RAHMAYANTI AGUSTINI YEAR 2022 - Rahmayanti Agustini; Nofa Anggriani (International Journal of Medicine and Health, 2023)
Background : The number of artificial gravidarum events in Indonesia obtained from 2,203 pregnancies which can be fully observed is 543 pregnant women exposed to gravidarum. In Indonesia about 10% of pregnant women get emesis from gravidarum. In east Java, emesis an gravidarum accounts for 10% - 15% of the number of pregnant mothers as much as 182,815 in 2015 (NHS, 2015). According to the initial survey carried out by researchers of 10 pregnant mothers in the girlfriend medical center, there are 8 people (80%) of pregnant mothers who emesis the gravidarum of the trimester I pregnancy and 2 (20%) who are not emesis by the gravidarum. A gravidarum emesis of this pregnancy can be attributed to external levels and a progesterone within the body (wiknjosastro, 2012).Management of nausea and vomiting can be done by non-pharmacological methods. Non-pharmacological therapies such as drinking boiled red ginger and coconut water. Red ginger contains zingiberol, zingiberene essential oil, curcumin, bisabillene, flandrene, gingerol, vitamin A which can reduce nausea and vomiting. Coconut water also contains minerals, namely magnesium, potassium and calcium. It turns out that drinking coconut water can relieve symptoms of nausea and vomiting. objective : It is known that theeffectivenessof giving coconut water and red gingerin the pregnant mother to drop in emesis gravidarum. Methods : Quasi experimental with a pretest protest design with a two experimental design. The samples in this study were all pregnant women at TBPM Rahmayanti in October – December 2022 as many as 30 people, the sampling technique was total sampling. Results : There is an effectiveness of giving coconut water and red ginger to pregnant women in reducing emesis gravidarum (p.value 0.000). Conclusions and Suggestions : Coconut water and red ginger decoction are both effective in reducing emesis gravidarum. Midwives are expected to provide counseling to pregnant women, how to make red ginger stew and drink coconut water to reduce emesis gravidarum.Reading Lists: 36 readings (2015-2021).